The Design and Life Test of a Multifunction Power Amplifier for Space Application - Xiuqin Xu; Hui Xu; Yongheng Shang; Zhiyu Wang; Yang Wang; Liping Wang; Hao Luo; Zhengliang Huang; Faxin Yu (Active and Passive Electronic Components)
A new multifunction power amplifier (MFPA) is designed and fabricated for the application of point-to-point K-Band backhaul TR module. A DC temperature life test was performed to model the up-limit temperature effect of the designed MFPA under space application. After 240 hours of 100°C life test, the test results illustrate that the designed MFPA has only slight power degradation at the saturation region without change of the linear gain. The general performance of the designed MFPA satisfies the requirement of the application scenario.